A comparison of the mixing thermodynamics of the antifluorite-structured Mg2Si1−xGex, Mg2Sn1−xGex and Mg2Si1−xSnx alloys from first principles. (March 2021) - Ektarawong, A.; Khamkaeo, S.; Alling, B.; Bovornratanaraks, T.
Abstract: The mixing thermodynamics of the antifluorite-structured Mg2 Si 1 − x Ge x is investigated using the first-principles calculations. We find that Mg2 Si and Mg2 Ge readily mix with each other leading to formation of a single-phase random solid solutions of Mg2 Si 1 − x Ge x across the entire composition range from the temperature of about 50 K and above. At 0 K, Mg2 Si 1 − x Ge x exhibits a weak energy preference toward local phase segregation into Mg2 Si and Mg2 Ge without forming any ordered patterns of Si and Ge atoms. Through a comparison with the mixing thermodynamics of Mg2 Sn with Mg2 Si or Mg2 Ge, a small lattice misfit between Mg2 Si and Mg2 Ge of less than 1 % is responsible for the formation of stable Mg2 Si 1 − x Ge x random solid solutions at such a low temperature. Besides their thermodynamic stability, our prediction reveals that the random solid solutions of Mg2 Si 1 − x Ge x are dynamically and mechanically stable. These findings justify the uses of structural models of Mg2 Si 1 − x Ge x, assuming a random distribution of Si and Ge atoms in the previous theoretical studies, and also provide an insight into the complete solubility of Mg2 Ge in Mg2 Si and vice versa at all temperature where the atomic diffusion is activated. Highlights: No ordered patterns of Si and Ge atoms in Mg2 Si 1 − x Ge x are predicted even at 0 K. Mg2 Si 1 − x Ge x displays an unusually weak tendency toward local phase segregation at 0 K. Mg2 Si 1 − x Ge x forms complete series of random solid solutions above 50 K. A small lattice misfit promotes formation of Mg2 Si 1 − x Ge x random solid solutions.